Fetal growth restriction: aetiology, screening, diagnosis and management - Augusthy, Valsa Chathampadathil (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2017)
Foetal growth restriction (FGR) is a pathological condition that refers to a foetus that fails to reach his/her genetically predetermined growth potential. FGR remains a leading contributor to perinatal mortality and morbidity and metabolic syndrome in later life. The purpose of this review is to provide the summary statements of the aetiology of FGR and to establish a framework for screening, diagnosis, and management of pregnancies affected with foetal growth restriction. For this study, published literature was retrieved through searches of PubMed (Medline), Highwire, Google Scholar, Scopus, Cochrane Database of Systematic Reviews. Conference/Seminar proceedings, textbooks, previously published systematic reviews, controlled clinical trials, high quality prospective and retrospective observational studies, research articles and unpublished studies were also used for this study. The identification of FGR begins with assessment of maternal, foetal, placental and environmental risk factors and the diagnosis is made by Ultrasound biometry examination. Functional assessment of placental and foetal circulation by Doppler velocimetry and blood flow volume, together with computerized assessment of foetal heart rate variability, are key examinations in early and late FGR to assess severity of the disease and monitor foetal wellbeing. Appropriate timing of delivery in early FGR might change the outcome, and appropriate monitoring in late and term FGR might avoid unnecessary interventions.